(untitled) (Damascus University Journal for engineering sciences, 2023)
The aim of this research essay is to identify Difficult Beauty concept, as one of the new philosophical concepts in aesthetics, which emerged as a result throughout Beauty concept changes since Art had been liberated from the prevailing Classism and its strict criteria, especially at the beginning of the twentieth century. Beauty perspective had been changed from what was prevailing, and modern artist tended to substitute old beauty concepts with new ones, more suitable to modern time and its utilities. The research discusses the relation between Difficult Beauty with Beauty and Ugliness. This controversial duality had played an eminent role in Difficult Beauty emergence. The research, In addition, discusses some modern sculptural works, couples in particular, which are considered difficult beauty works and identified through being analyzed by applying difficult beauty elements on them, to approach the demanded results. In research conclusion, there was a need to compare between Terrible Beauty as a contemporary expression and the Difficult Beauty which is still being used in contemporary works.